English and Malay text messages and what they say about text and cultures - Catherine, Walter; Ernisa, Marzuki (Scientific Research, 2013)
This study of the pragmatics of cross-cultural text messages throws light on the evolution of new hybrid forms of literacy and on the complex ways that culture is expressed and mediated in second language/second culture contexts. An investigation was carried out into the pragmatics of apology in first-language (L1) and second-language (L2) short messaging service text messages of adult Malay speakers who are proficient users of English, living and studying in an English-speaking university environment; and into L1 English users’ text apologies in the same context. Research questions included whether these proficient L2 English users would perform differently from L1 English users in this high-stakes speech act, and from their own L1 Malay use; and whether apologies in what has been called a hybrid medium would differ from those previously studied in writing, in speech and in other electronic media. Twenty-six native speakers of English and 26 native speakers of Malay responded via text messages to discourse completion tests (DCTs) in L1; the DCTs represented either high or low levels of offence calling for apologies. The Malay native speakers also responded to apology situations in L2 English. Data were coded using an adapted version of Cohen and Olshtain’s (1981) coding scheme. Analysis of the messages sent by participants revealed clear signs of a hybrid type of text that is differently conceptualised by the two communities. It also showed that the Malay users’ second language literacy was shaped in a complex way that sometimes accommodated the second language/second culture and sometimes retained first language/first culture values.